1999
DOI: 10.1074/jbc.274.4.2446
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Collagenase-3 (MMP-13) Expression in Human Skin Fibroblasts by Three-dimensional Collagen Is Mediated by p38 Mitogen-activated Protein Kinase

Abstract: Collagenase-3 (matrix metalloproteinase-13, MMP-13) is a recently identified human MMP with an exceptionally wide substrate specificity and restricted tissue-specific expression. Here we show that MMP-13 expression is induced in normal human skin fibroblasts cultured within three-dimensional collagen gel resulting in production and proteolytic activation of MMP-13. Induction of MMP-13 mRNAs by collagen gel was potently inhibited by blocking antibodies against ␣ 1 and ␣ 2 integrin subunits and augmented by acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
219
6
4

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 267 publications
(238 citation statements)
references
References 54 publications
9
219
6
4
Order By: Relevance
“…For EV1 infections MOI 100 was used. have previously shown that mitogen activated protein kinases (MAPKs) are regulated by the collagen receptor integrins (Ravanti et al, 1999). Here, extracellular signal regulated kinase (ERK) was activated at very early time points after ␣2␤1 binding to EV1 ( Figure 5A).…”
Section: Protein Kinase C Activity Is Essential For the Internalizatimentioning
confidence: 81%
See 1 more Smart Citation
“…For EV1 infections MOI 100 was used. have previously shown that mitogen activated protein kinases (MAPKs) are regulated by the collagen receptor integrins (Ravanti et al, 1999). Here, extracellular signal regulated kinase (ERK) was activated at very early time points after ␣2␤1 binding to EV1 ( Figure 5A).…”
Section: Protein Kinase C Activity Is Essential For the Internalizatimentioning
confidence: 81%
“…Molecular Biology of the Cell 634 (Ivaska et al, 1999;Ravanti et al, 1999), the isoform of PKC (PKC ; Xu and Clark, 1997), and protein phosphatase 2A (PP2A; Ivaska et al, 2002a). Here, PKC␣ activity was needed for the internalization of ␣2␤1 integrin in caveolae.…”
Section: P Upla Et Almentioning
confidence: 99%
“…Recently, three-dimensional collagen lattices were demonstrated to stimulate MMP-13 and collagen gene expression via activation of p38 MAPK [18,19]. Thus we used SB203580, a specific inhibitor of p38 (p38α) and p38β [26], to study the role of p38 MAPK in the expression of MMP-1, another injury-related gene…”
Section: Human Dermal Fibroblasts Treated With Sb203580 Results In a mentioning
confidence: 99%
“…Several studies have also reported that the p38 MAPK is required for the induction of MMP-1 gene expression by ceramide and tumour-derived extracellular matrix metalloproteinase inducer (EMMPRIN) [20,21]. Interestingly, although contracting collagen lattices induce both activation of p38 MAPK [18] and expression of MMP-1 [3,22] in human fibroblasts, the complete inhibition of p38 MAPK by SB203580 at 10 µM does not result in appreciable suppression of MMP-1 expression [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation